Democratic Republic of Timor-Leste : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The recent rise in inflation in Timor-Leste has raised concerns about international competitiveness and the cost of living. After remaining relatively subdued for several years, inflation in Timor-Leste rose decisively over the past two years. Higher food prices account for most of the increase in the consumer price index (CPI) in 2006-07. In contrast, the pace of non-food CPI inflation decelerated slightly in 2007, to below 3.5 percent on average. Further, based on Q1 2008 data, the second-round impact of oil price increases on inflation is emerging.